Pengaruh Pembayaran Cashless Dengan Sistem QR Code, Perceived Trust Dan Perceived Ease Of Use Terhadap Kepuasan Pengguna ShopeePay (Studi Kasus Pada Konsumen Mie Gacoan Kota Malang) - Dwi Riska Amalia; Muhammad Ridwan Basalamah; Tri Sugiarti Ramadhan (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Since the Covid-19 pandemic until after the Covid-19 pandemic, consumer habits have changed in making transactions using digital wallets or e-wallets. One of the e-wallets that is currently being widely used is ShopeePay. ShopeePay can be used for cashless payments using the Quick Response Code (QR Code) which is considered more practical. The purpose of this study was to find out and analyze cashless payments with the QR Code, perceived trust and perceived ease of use on ShopeePay user satisfaction. The population in this study were City students Malang, which uses the ShopeePay e-wallet. Determination of the number of samples in this study uses the Malhotra formula and the results obtained are 70 respondents. The approach method uses a non-probability sampling technique, namely purposive sampling which uses a sample collection technique based on certain criteria. The results show that simultaneously and partially cashless payments with QR Code, perceived trust and perceived ease of use have a significant effect on ShopeePay user satisfaction. Keywords: Cashless Payment With QR Code, Perceived Trust And Perceived Ease Of Use, Shopeepay User Satisfaction